THE ROLE OF WTO AND INTERNATIONAL COOPERATION ON SERVICES TRADE POLICY - Alina HAGIU; Marinela BARBULESCU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2019)
In the last decades most of the countries of the world have been adopting reforms regarding the increase of competition in their service markets motivated by the benefits regarding both the standard of living and overall economic competitiveness. Meanwhile, services have started to have an increasing share of GDP, demand for international services has increased and new demand is emerging. Governments cooperate regarding services trade policy because the landscape of services trade has evolved and transformed, present demand for internationally supplied services has increased, services economy has evolved from a model in which governments were solely and uniquely responsible for the supply of many infrastructural and social services to one where these services are provided also, or predominantly, by private actors in competition with each other, and because “going it alone” doesn’t allow all potential benefits to be reaped. The aim of this paper is to clarify why governments cooperate on services trade policy and why regulatory cooperation matters for business, to present how countries collaborate in the services sphere, to present the potential of trade in services for developing countries and to identify prospects for future cooperation.